ANALISIS PENGARUH KUALITAS PELAYANAN, KEPERCAYAAN DAN KEPUASAN PELANGGAN TERHADAP LOYALITAS NASABAH TABUNGAN PADA BANK BCA KCP KOTA WISATA - Amelia Virsyasari Susanto, (2022)
Increasing competition in the banking sector makes it necessary for BCA KCP Kota Wisata bank to continue to maintain service quality, trust, and customer satisfaction in order to create customer loyalty for BCA KCP Kota Wisata bank savings. This research is a quantitative study to determine, prove, and analyze: (1) the effect of service quality on customer loyalty savings at the BCA KCP Kota Wisata bank (2) the influence of trust on the loyalty of savings customers at the BCA KCP Kota Wisata bank (3) the influence of customer satisfaction on the loyalty of savings customers at the BCA KCP Kota Wisata bank. The population used is BCA KCP Kota Wisata bank savings customers. The research data was obtained by distributing questionnaires via google form to 75 respondents through purposive sampling method. The analysis technique uses Partial Least Square (PLS). As for the results obtained, (1) service quality has a positive and significant effect on customer loyalty with a coefficient value of 0.299 (2) trust has a positive and significant effect on customer loyalty of 0.245 (3) customer satisfaction has a positive and significant effect on customer loyalty with a coefficient value of 0.449. With the value of the independent variables jointly affecting customer loyalty by 0.874 or in percentage of 87.4% and in the remaining percentage of 12.6% caused by other factors.